The Role of Hadith in Determining Islamic Economic Law: A Study of Economic Hadiths in Sahih Bukhari and Muslim - Aini, Siti Noor (Journal of Noesantara Islamic Studies, 2024)
Islamic economic law is deeply rooted in the primary sources of Islamic jurisprudence: the Qur'an and Hadith. While the Qur'an provides the foundational principles, the Hadith offers detailed guidance on economic transactions and ethics. Economic Hadiths, particularly from Sahih Bukhari and Sahih Muslim, are essential for shaping legal rulings in Islamic finance and commerce. However, the influence of these Hadiths on Islamic economic law is underexplored. This study analyzes the role of economic Hadiths in Sahih Bukhari and Sahih Muslim in shaping Islamic economic law. Using a qualitative content analysis approach, the study categorizes key economic Hadiths into themes such as trade ethics, prohibition of interest (riba), partnerships, and fairness in transactions. A comparative analysis assesses how these themes have been interpreted in both classical and contemporary Islamic economic jurisprudence. The findings show that economic Hadiths significantly impact Islamic economic law by offering detailed rulings on business ethics, contracts, and financial partnerships. Core principles like fairness, transparency, and risk-sharing are highlighted. The study concludes that Hadiths play a crucial role in complementing Qur'anic guidance, providing practical frameworks for financial activities, and balancing ethics with legal rulings in Islamic economic law.